It’s About Bloody Time and Space - Inniss, Lolita Buckner (Columbia Journal of Gender and Law, 2021)
Time frames relationships of power, especially in the context of law. One of the clearest ways in which time is implicated in both law and society is via discourses about women’s biological functions. This Article is an introduction to a larger project that analyzes legal discourses regarding a crucial aspect of women’s calendrically-associated biological functions: women’s menstrual periods. Over the course of the project, I explore legal discourses about menstruation through the notion of what literary theorist Mikhail Bakhtin calls “chronotopes”—a connectedness of temporal and spatial relationships. Temporality, Bakhtin argues, is closely associated with certain paradigmatic spaces, and the combination of shapes, ideologies, and identities. Legal discussions of women’s menstrual bleeding are key sites for the discursive creation and maintenance of certain ideologies of womanhood. These discussions appear in a wide variety of contexts and in ways that either explicitly reference or implicitly index ideologies of female identity. All are characterized by efforts to mark them as narratives linked to other temporally prior or future moments, and are often indices of chronologically or spatially related stigmas and taboos. While legal discourses of menstruation do not give a complete account of the category “woman,” they provide cogent examples of how womanhood ideologies are constructed in legal contexts.